Preventive drug therapy and contralateral breast cancer: summary of the evidence of clinical trials and observational studies. (2nd November 2019) - Bens, Annet; Langballe, Rikke; Bernstein, Jonine L.; Cronin-Fenton, Deirdre; Friis, Søren; Mellemkjaer, Lene
Abstract: Background: Breast cancer patients have a lifelong 2–4-fold increased risk of developing a second primary tumor in the contralateral breast compared with the risk for a first primary breast cancer in the general female population. Prevention of contralateral breast cancer (CBC) has received increased attention during recent decades. Here, we summarize and discuss the available literature on drug preventive therapy and CBC. Results: The endocrine-targetting drugs, tamoxifen and aromatase inhibitors are used as standard adjuvant treatment for estrogen receptor (ER)-positive breast cancer. Both are associated with relative risk reductions of CBC of up to 50%, but incur serious side effects. Several prescription drugs originally developed for other purposes, including bisphosphonates, statins, non-steroidal anti-inflammatory drugs, metformin, anti-hypertensives and retinoids, have shown anti-cancer activity in preclinical models. However, results of observational studies on CBC are sparse and inconsistent, with only statins demonstrating promise as preventive agents and a potential treatment option for ER-negative breast cancer patients. Conclusion: Future studies are needed to assess the effect of statins in risk reduction and to identify other drugs with chemopreventive potential against CBC. Eventually, efforts must be directed towards identifying those breast cancer patients likely to benefit most from specific preventive therapies.